Goeppertia mendesiana sp nov (Marantaceae) from Bahia, Brazil, with a key to the species of Goeppertia with ornamented leaves in the Atlantic Forest of Brazil - Saka, Mariana Naomi [UNESP]; Popovkin, Alex V. (Wiley-Blackwell, 2017)
Goeppertia mendesiana, a new species from the Atlantic Forest of Bahia, Brazil, is described and illustrated. It resembles G. widgrenii (Korn.) Borchs. & Suarez, but differs from that species by its villose petioles and peduncles (vs glabrous in G. widgrenii) and by the absence of bracteoles and interphylls, a rare feature in the genus. The ecology, distribution and conservation status of the new species is presented, along with a key to the species of Goeppertia with ornamented leaves in the Atlantic Forest of Brazil.